Design Of Air Pollution Monitoring Tools In Surabaya Area Based On Nodemcu - Fajar Andhika Putra (International Journal of Computer, Network Security and Information System, 2020)
According to data from the Central Bureau of Statistics in 2017, traffic density in Indonesia is dominated by motorbikes, with a total of 113,030,793 units, followed by private cars with 15,493,068 units, freight cars and buses. Apart from vehicles, the presence of motorized vehicles that keeps popping up has the potential to cause an increase in air pollution. This encourages to create an air pollution measuring device, where the data obtained from this tool will be sent to an application that can be used by the public. There have been many studies related to air pollution detection before. The system that is made relies on the MCU node as a data processing center. Then send data that has been captured by the sensor and processed by the MCU node using a WIFI signal. This study uses 3 sensors to detect air pollution, namely mq2 and mq9, both sensors are sensitive to gas leaks such as smoke, CO, and propane. There are 4 pins on this sensor, namely VCC, A0, D0, and ground. Of the four pins, only pin D0 will not be used because they want more accurate data. By using radio signals, this tool will be able to transmit pollution and vehicle density data directly to the monitoring center.